EFFECT OF FINANCIAL PERFORMANCE AGAINST MARKET PERFORMANCE IN BANKING - Desry Ponisa Putra; Seto Sulaksono Adi Wibowo (Pusat P2M Politeknik Negeri Batam, 2018)
This study aims to examine the effect of the financial performance of the banking market performance. This study used a sample of banking companies listed in Indonesia Stock Exchange 2011-2013. Financial Kineja measured using CAMEL (Capital, Asset Quality, Management, Earnings and Liquidity). market-based financial performance is measured by stock returns, variable we used in this study are the independent variables which covers CAR, DER, ROA, LDR. Data research using panel data and methods of data analysis using simple linear regression. influence the financial performance against the performance of the market is not particularly a significant impact on the performance of banks.